Monetary conservatism and fiscal policy - Klaus Adam; Roberto M. Billi (European Central Bank (ECB), 2006)
Does an inflation conservative central bank à la Rogoff (1985) remain desirable in a setting with endogenous fiscal policy? To provide an answer we study monetary and fiscal policy games without commitment in a dynamic stochastic sticky price economy with monopolistic distortions. Monetary policy determines nominal interest rates and fiscal policy provides public goods generating private utility. We find that lack of fiscal commitment gives rise to excessive public spending. The optimal inflation rate internalizing this distortion is positive, but lack of monetary commitment robustly generates too much inflation. A conservative monetary authority thus remains desirable. Exclusive focus on inflation by the central bank recoups large part - in some cases all - of the steady state welfare losses associated with lack of monetary and fiscal commitment. An inflation conservative central bank tends to improve also the conduct of stabilization policy.
Keywords: E52; E62; E63; 330; conservative monetary policy; discretionary policy; sequential non-cooperative policy games; time consistent policy; Geldpolitik; Inflationsrate; Regelbindung versus Diskretion; Zentralbank; Finanzpolitik; Öffentliche Ausgaben; Wohlfahrtsanalyse; Wirtschaftsmodell